Diseño de prototipo utilizando caucho granulado como material alternativo para estructuras de pavimentos en vías de Manabí San Vicente - Paladines Unuzungo, Verónica Lilibeth (2024)
In the province of Manabí, specifically in San Vicente, roads face significant challenges related to the durability and resistance of traditional asphalt mixtures, resulting in an increase in road design and maintenance costs. Factors such as the presence of potholes, the abrasive action of saline sand and unpaved sections are common in this region, rapidly deteriorating road infrastructure. Given this problem, the need arises to explore alternatives in the materials used in road construction, with the aim of optimizing asphalt mixtures and improving their long-term performance. One proposed solution is the incorporation of alternative materials, such as crumb rubber from recycled tires, into the asphalt mix. This innovation not only seeks to improve the resistance and durability of asphalt, but also offers economic and environmental benefits. By reusing materials that would otherwise be discarded, the need for expensive raw materials is reduced and recycling is promoted, contributing to the sustainability of the project....